Uso de rocurônio, pancurônio e atracúrio em Podocnemis expansa (Schweigger, 1812) (Testudines, Podocnemididae) - Bosso, Andréa Cristina Scarpa (2008)
CHAPTER I: Pharmacological restraint of chelonians is a necessary procedure in zoos or in the treatment of wild and exotic animals. With the purpose of describing the results and side effects of the rocuronium restraint in Podocnemis expansa, twenty commercially bred P. expansa, weighing on average 1.59 ± 0.28 kg, were subjected to two protocols: G1 was given 0.25 mg/kg IM of rocuronium and 0.07 mg/kg IM of neostigmine, while G2 received 0.50 mg/kg IM of rocuronium and 0.07 mg/kg IM of neostigmine. The drugs were applied, respectively, in the left and right thoracic members. Assessments were made of the anesthetic parameters of respiratory frequency, heartbeat, righting reflex, cloacal relaxation, palpebral and pupilar reflexes, easy handling, muscle relaxation, locomotion, response to pain. CHAPTER II: Pharmacological restraint of chelonians is a necessary procedure in zoos or in the treatment of wild and exotic animals. With the purpose of describing the results and side effects of the pancuronium restraint in Podocnemis expansa, twenty commercially bred P. expansa, weighing on average 1.58 ± 0.40 kg, were subjected to two protocols: G1 was given 0.02 mg/kg IM of pancuronium and, if necessary, 0.07 mg/kg IM of neostigmine, while G2 received 0.04 mg/kg IM of pancuronium and 0.07 mg/kg IM of neostigmine. The drugs were applied, respectively, in the left and right thoracic members. Assessments were made of the anesthetic parameters of respiratory frequency, heartbeat, righting reflex, cloacal relaxation, palpebral and pupilar reflexes, easy handling, muscle relaxation, locomotion, and response to pain stimuli in the right thoracic members, pelvic members and tail, as well as ambient humidity and temperature. A consistent neuromuscular blockade effect was recorded only in five turtles after 20 ± 7.07 minutes in G1 and 15 ± 5.27 minutes in all members of G2. All the animals were recovered in 180 minutes. The pancuronium in the doses 0.04 mg/kg IM in P. expansa is safe and effective as support of pre-anesthetic and clinical procedures, observing itself complete muscular relaxation, easy of manipulation and loss of the capacity of locomotion in dose-dependent times. Dose 0.02 mg/kg IM presented satisfactory effects in 50% of the animals quizzed, considered helpful for facilitate physical exams, collection of biological samples and others painless procedures. CHAPTER III: Pharmacological restraint of chelonians is a necessary procedure in zoos or in the treatment of wild and exotic animals. With the purpose of describing the results and side effects of the pancuronium restraint in Podocnemis expansa, twenty commercially bred P. expansa, weighing on average 2.13 ± 0.50 kg, were subjected to two protocols: G1 was given 0.60 mg/kg IM of atracurium and 0.07 mg/kg IM of neostigmine, while G2 received 0.80 mg/kg IM of atracurium and 0.07 mg/kg IM of neostigmine. The drugs were applied, respectively, in the left and right thoracic members. Assessments were made of the anesthetic parameters of respiratory frequency, heartbeat, righting reflex, cloacal relaxation, palpebral and pupilar reflexes, easy handling, muscle relaxation, locomotion, and response to pain stimuli in the right thoracic members, pelvic members and tail, as well as ambient humidity and temperature. A consistent neuromuscular blockade effect was recorded only in five turtles after 20 minutes in G1 and 13.33 ± 5 minutes in nine members of G2. All the animals were recovered in 150 minutes in G1 and 280 minutes in G2. The atracurium in the doses 0.60 mg/kg IM presented satisfactory effects in 50% of the animals quizzed, considered helpful for facilitate physical exams, collection of biological samples and others painless procedures. Despite of the dose of 0.80 mg/kg IM presented satisfactory neuromuscular blockade in nine animals quizzed, observing itself muscular relaxation, facility of manipulation and loses of the capacity of locomotion, diverse side effects occurred and one didn t present satisfactory and complete blockade. With that, we recommend more studies before of this drug to be utilized in the routine. stimuli in the right thoracic members, pelvic members and tail, as well as ambient humidity and temperature. A consistent neuromuscular blockade effect was recorded after 12 ± 4.21 minutes in G1 and G2. All the animals were recovered in 150 minutes. The rocuronium in the doses 0.25 and 0.50 mg/kg IM in P. expansa is safe and effective as support of pre-anesthetic and clinical procedures, observing itself complete muscular relaxation, easy of manipulation and loss of the capacity of locomotion in dose-dependent times. They were not found statistical differences between the doses for the majority of the assessments. G1 was as efficient as G2.